2014
DOI: 10.1890/13-1848.1
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected phenological responses of butterflies to the interaction of urbanization and geographic temperature

Abstract: Urbanization and global climate change can profoundly alter biological systems, yet scientists often analyze their effects separately. We test how the timing of life cycle events (phenology) is jointly influenced by these two components of global change. To do so, we use a long‐term phenological data set of 20 common butterfly species from 83 sites across the state of Ohio, USA, with sites that range from rural undeveloped areas to moderately sized cities. These sites span a latitudinal gradient in mean temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 41 publications
6
69
1
Order By: Relevance
“…However, contrary to these results, an analysis of central European Lepidoptera by Altermatt () suggests that there has been a delay in phenology of late‐flying lepidopteran species since 1980. Diamond et al () found that several butterfly species occupying urban environments in Ohio, USA, also exhibited delayed phenology in response to rising temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to these results, an analysis of central European Lepidoptera by Altermatt () suggests that there has been a delay in phenology of late‐flying lepidopteran species since 1980. Diamond et al () found that several butterfly species occupying urban environments in Ohio, USA, also exhibited delayed phenology in response to rising temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the appearance of 28 European butterfly species in human settlements is 9–10 d later than in forests and agricultural areas (Altermatt ), and urbanization is associated with phenological delays in first and peak appearance dates of several North American butterfly species (Diamond et al. ). The dates of arboreal caterpillar biomass peaks, however, did not differ consistently between an urban parkland area and a woodland habitat in central Poland (Wawrzyniak et al.…”
Section: Introductionmentioning
confidence: 99%
“…Phenological studies have typically involved measures such as mean first encounter, mean peak encounter and mean length of the flight period (Roy and Sparks 2000;Diamond et al 2014;Karlsson 2014), which may be driven by observer behaviour. The improved estimates of phenology from dynamic models provide the opportunity to study linkages between changes in phenology and changes in abundance and productivity, for example phenological mismatch (Hindle et al 2015).…”
Section: Discussionmentioning
confidence: 99%